2013
DOI: 10.1080/07294360.2013.777033
|View full text |Cite
|
Sign up to set email alerts
|

Use and evaluation of a technology-rich experimental collaborative classroom

Abstract: In order to pilot a shift towards greater use of collaborative learning in our higher education programs, the University of Hong Kong has invested in the development of a prototype technology-enhanced collaborative learning space. The space was created by retrofitting a vacant studio, turning it into an innovative classroom space in which collaborative learning is promoted and facilitated both through the provision of technology and by the physical layout of the room. We have used the space to pioneer collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…A study by Salter et al (2013) explored the effect of a unique collaborative design layout on collaboration as well as the use of technology. An entire building of collaborative spaces was constructed on their campus, each space of which being designed with different nonstandard shapes and layouts.…”
Section: Connectedness Through Visual Relationshipsmentioning
confidence: 99%
“…A study by Salter et al (2013) explored the effect of a unique collaborative design layout on collaboration as well as the use of technology. An entire building of collaborative spaces was constructed on their campus, each space of which being designed with different nonstandard shapes and layouts.…”
Section: Connectedness Through Visual Relationshipsmentioning
confidence: 99%
“…Similar to the case study conducted by Salter and colleagues [10], a team of academics from JCU are researching the new 'networked' learning space. The cross-disciplinary team consists of representatives from Arts and Social Sciences, Business, Tourism and Information Technology, and Education.…”
Section: A Learning Space At Jcu Singaporementioning
confidence: 99%
“…Salter and colleagues [10] reviewed past studies that demonstrated the usefulness and effectiveness of technology rich collaborative learning space or 'networked' classrooms on the impact of students' learning. For instance, collaborative learning spaces have been found to strengthen social interaction between students and to maintain an active learning attitude during curriculum [11].…”
Section: Wlts and Spaces Of Learningmentioning
confidence: 99%
See 2 more Smart Citations